(untitled) - Samarah Nazar; Shireen Gul; Saira Sonam (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The aim of the study is to draw a comparison of selected novels by British-American author Ahmed Salman Rushdie by doing narrative and semantic analysis. ’Languages of Truth’ is a compilation of Salman Rushdie’s essays and speeches delivered during the course of his career. ’Imaginary Homelands’ is an anthology of essays and critical analysis. The purpose of this analysis is also to assess the merits and shortcomings of the book, as well as its semantic network of ’Imaginary Homelands’ and ’languages of truth’. The article also provides details how to place ’Imaginary Homelands’ within the broader framework of its subject area, contrasting it with ’Languages of truth’ and noting its contributions to the field. The qualitative approach taken here sheds light on several facets of both "Imaginary Homelands" and "Languages of Truth," as the title of this study suggests. Metaphor, narrative structure, textual register, and organizational system are only few of the areas where the two writings are compared and contrasted. This study also elaborates the commonalities, both "Languages of Truth" and "Imaginary Homelands", share in their focus on language and identity, as well as their use of cultural study, literary criticism, and introspective writing. The study identifies the reasons Rushdie’s books have captivated readers all over the world.